2007
DOI: 10.1044/0161-1461(2007/025)
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual Children’s Language Abilities and Early Reading Outcomes in Head Start and Kindergarten

Abstract: Purpose-The purpose of this study was to investigate the relationship between Head Start children's receptive language development and their kindergarten reading outcomes.Method-Eighty-eight bilingual children who were eligible to attend Head Start for 2 years participated in the study. Growth curve models were used to examine the relationship between children's language abilities during 2 years in Head Start and end-of-kindergarten reading outcomes.Results-The results revealed that children's English and Span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
128
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(142 citation statements)
references
References 33 publications
12
128
2
Order By: Relevance
“…The research by Hammer et al (2006b) and Oller and Eilers (2002) on the oral language development of bilingual children supports the argument that the timing of exposure to English in relation to school entry impacts their development. When focusing on bilingual preschoolers, Hammer et al (2006b) demonstrated that children with HEC had higher initial overall English receptive language abilities than children who did not experience English communication (SEC) until school entry.…”
Section: Implications For Oral Languagesupporting
confidence: 49%
See 4 more Smart Citations
“…The research by Hammer et al (2006b) and Oller and Eilers (2002) on the oral language development of bilingual children supports the argument that the timing of exposure to English in relation to school entry impacts their development. When focusing on bilingual preschoolers, Hammer et al (2006b) demonstrated that children with HEC had higher initial overall English receptive language abilities than children who did not experience English communication (SEC) until school entry.…”
Section: Implications For Oral Languagesupporting
confidence: 49%
“…The results of these analyses (Hammer et al, 2006b) revealed that the children's letter-word identification abilities were at the test mean in English at the end of kindergarten, with no differences between the HEC and SEC groups. Both groups of children had Spanish letterword identification abilities that were close to 1 SD below the test mean.…”
Section: Research On Outside-in Factors With Bilingual Childrenmentioning
confidence: 91%
See 3 more Smart Citations